2014
DOI: 10.1093/nar/gku286
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RNA-binding analysis of the trypanosome U1 snRNP proteins U1C and U1-70K reveals cis/trans-spliceosomal network

Abstract: Trans-splicing in trypanosomes adds a 39-nucleotide mini-exon from the spliced leader (SL) RNA to the 5′ end of each protein-coding sequence. On the other hand, cis-splicing of the few intron-containing genes requires the U1 small nuclear ribonucleoprotein (snRNP) particle. To search for potential new functions of the U1 snRNP in Trypanosoma brucei, we applied genome-wide individual-nucleotide resolution crosslinking-immunoprecipitation (iCLIP), focusing on the U1 snRNP-specific proteins U1C and U1-70K. Surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
2
10
0
1
Order By: Relevance
“…A recent study from our group supports the hypothesis that cis splicing may be an evolutionary relic. 11 The findings presented here further support this provocative idea. In trypanosomes only two genes contain intron sequences and require cis splicing for proper mRNA maturation: Tb927.3.3160 and Tb927.8.1510, the latter of which codes for an ATP-dependent DEAD box helicase.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…A recent study from our group supports the hypothesis that cis splicing may be an evolutionary relic. 11 The findings presented here further support this provocative idea. In trypanosomes only two genes contain intron sequences and require cis splicing for proper mRNA maturation: Tb927.3.3160 and Tb927.8.1510, the latter of which codes for an ATP-dependent DEAD box helicase.…”
Section: Discussionsupporting
confidence: 80%
“…However, we recently reported that the U1 snRNP may also associate with the trans-spliceosome, indicating a physical linkage between cis-and trans-splicing. 11 Taken together this suggests that the U1 snRNP functions in both splicing and polyadenylation, likely linking both processes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…TT sites compare favorably to all other tested noncanonical dinucleotides (except GC). Frequently, TT sites possess an extra GT at position −1 potentially providing stabilizing effects exerted by SNRPC (Rosel et al 2011;Preußer et al 2014) and LUC7-like. Indeed, in our RNA-seq data set, 37/41 high-confidence noncanonical non-GC 5 ′ ss-in particular all TT sites-contained at least one GT dinucleotide.…”
Section: Allmentioning
confidence: 99%